Word-of-mouth intent in the restaurant industry of Mexico, a structural equation modeling approach mediated by customer satisfaction - Reich López, Christian; Terán Cázares, María Mayela (Facultad de Contaduría Pública y Administración U.A.N.L., 2022)
This research aims to analyze the variables that are related to word-of-mouth intention in a context of full-service restaurants, considering as a mediating variable customer’s satisfaction. Partial least squares- structural equation modeling was the chosen approach to test hypotheses. Regarding results, customer’s satisfaction indeed mediates the direct effects of the variables related to word-of-mouth intention thus, these variables impact both customer satisfaction and word-of-mouth intention, the aim of this research was Monterrey’s metropolitan area.